SICKLE CELL ANEMIA: CHARACTERIZATION OF THE PATIENTS ATTENDED IN A SPECIALIST OUTPATIENT CENTER - Pâmella Naiana Dias dos Santos; Márcia Helena de Souza Freire; Gisele Basso Zanlorenzi; Mara Albonei Pianovski; Vanilda de Fátima de Andrade Matos Denardi (Universidade Federal do Paraná, 2014)
This qualitative research aimed to describe the clinical, social and demographic profile of patients with sickle cell anemia attended in a specialist outpatient center for Pediatric Hematology in Curitiba, Paraná. Between the 1st and 19th of October 2012, all the medical records of persons with hemoglobinopathies in the outpatient center were sought; 58 persons were identified who met the inclusion criteria. Data from case histories and clinical tests, from the first attendance up to the date of collection, were organized in categories. There was a predominance (76%) of children (1 to 12 years old), originating from 14 health regions in the state (70.5%), diagnosed in the first year of life (80%), monitored for three years or more (86.2%), with clinical signs of skin paleness (94.8%) and fever (93.1%), with pain crisis as the main complication (70.7%). The results may support planning and operations in the care of the patient with sickle cell anemia and her family members in this outpatient service and also in other similar services.